Analysis and modeling of micro turbojets: a comprehensive model based on multiphysics principles. - Villarreal Valderrama, José Francisco (2019)
The Development of accurate models to represent turbojet performance is presented as a tool to meet the growing need for reliable unmanned aerial vehicle propulsion systems.